1972
DOI: 10.1680/geot.1972.22.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Inherent anisotropy in a sand

Abstract: Present knowledge of inherent anisotropy is reviewed and the development of a cubical triaxial cell for studying the inherent anisotropy of non-cohesive granular materials is described. This apparatus is unusual as it offers potential independent control of the three principal stresses through flexible stress controlled boundaries, and some discussion of the relative merits of different types of true triaxial cells is offered. Uniform local strain distributions were measured radiographically and favourable com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(145 citation statements)
references
References 12 publications
7
136
0
2
Order By: Relevance
“…Similar observations have been reported by Arthur and Menzies (1972) in cubical triaxial tests on tilted samples, Oda et al (1978) in plane strain tests, Arthur et al (1981) in directional shear cell tests and Cai et al (2013) in HCA tests.…”
Section: 11! Stress-strain Behavioursupporting
confidence: 89%
See 2 more Smart Citations
“…Similar observations have been reported by Arthur and Menzies (1972) in cubical triaxial tests on tilted samples, Oda et al (1978) in plane strain tests, Arthur et al (1981) in directional shear cell tests and Cai et al (2013) in HCA tests.…”
Section: 11! Stress-strain Behavioursupporting
confidence: 89%
“…Hence, soil anisotropy has attracted long-lasting interest of researchers and practitioners. Arthur and Menzies (1972) reviewed several early studies on the soil anisotropy. They prepared samples in a tilting mould to give different directions of sample deposition with respect to the applied principal stress directions, and found the specimen produced by pouring through air in one direction corresponded to a strength and pre-failure stress-strain anisotropy.…”
Section: ! Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experiments by Al-Tabbaa (1984), Arthur and Menzies (1972), Arthur et al (1977) and others showed that even initially isotropic soils could develop induced anisotropy. This had been defined by Casagrande and Carillo (1944) as anisotropy associated with a history of shearing strain.…”
Section: Preamblementioning
confidence: 97%
“…Strength anisotropy is of key engineering importance in estimating the stability of infrastructures and has therefore attracted much research interest. Extensive efforts of experimental testing and constitutive modelling have been made to better estimate the strength and deformation of anisotropic granular soils [2,3,5,6,9,19,22,27,29,32,34,42]. Experiments have been carried out by preparing and testing specimens of different tilting angles or loading a soil specimen along various directions [20,29,30,45].…”
Section: Introductionmentioning
confidence: 99%